Identification of a Novel TECTA mutation in a Chinese DFNA8/12 family with prelingual progressive sensorineural hearing impairment. - Zhengyue Li; Yilian Guo; Yu Lu; Jianzhong Li; Zhanguo Jin; Hongbo Li; Yanping Lu; Pu Dai; Dongyi Han; Jing Cheng; Huijun Yuan (PLoS ONE, 2013)
Tectorial membrane, an extracellular matrix of the cochlea, plays a crucial role in the transmission of sound to the sensory hair cells. Alpha-tectorin is the most important noncollagenous component of the tectorial membrane and the otolith membrane in the maculae of the vestibular system. Defects in TECTA, the gene encodes alpha-tectorin, are cause of both dominant (DFNA8/12) and recessive (DFNB21) forms of deafness. Here, we report a three-generation Chinese family characterized by prelingual progressive sensorineural hearing impairment. We mapped the disease locus to chromosome 11q23-24 region, overlapping with the DFNA8/12 locus. Sequencing of candidate gene TECTA revealed a heterozygous c.5945C>A substitution in exon 19, causing amino acid substitution of Ala to Asp at a conservative position 1982. The A1982D substitution is consistent with hearing loss in this Chinese family and has not been found in 200 random control chromosomes. To our knowledge, this is the first TECTA mutation identified in Chinese population. Our data provides additional molecular and clinical information for establishing a better genotype-phenotype understanding of DFNA8/12.